Coincidence detection using spiking neurons with application to face recognition - Kamaruzaman, Fadhlan; Shafie, Amir Akramin; Mohd Mustafah, Yasir (Hindawi Publishing Corporation, 2015)
We elucidate the practical implementation of Spiking Neural Network (SNN) as local ensembles of classifiers. Synaptic time constant